O ciberjornal como instrumento de ensino: Da teoria à prática - Zamith, Fernando (2004)
During this presentation we intend to show the interdisciplinary work that culminated in the creation of the cyberjournal JornalismoPortoNet (JPN) in March 2004. The primary purpose of JPN was to provide an academic training post for last term students, simulating the editorial office of a newspaper. Taking advantage of the interdisciplinary and human resources of the course, a scheme has been implemented for editing and publishing news material, involving teachers from particular fields of Design, Computer Science and Journalism. The idea was to make the most of the potentialities offered by internet, choosing news building structures to suit this new process (open, in tree, multilinear, and with parallel linkages), by means of text blocks hyperconnected to one another. The goals proposed in this initial phase of JPN which lasted until the first days in June were globally reached. Although JPN was not widely advertised, its visibility was good, reaching some twenty thousand visits in the two and half months of intensive work. In all, more than 900 articles and dozens of radio and television reports were prepared and transmitted. These results make the authors conclude that the cyberjournal is an excellent tool in Journalism teaching, considering its low production and distribution costs and the internet potentialities as medium of communication wherein all the other media converge.